PASCAL ON APPLICATIONS USING FIXED ASSETS DEPRECIATION TOTAL NUMBER OF YEAR - Yulianih Yulianih; Hariyanto Hariyanto, SKom, MM (Jurnal Sistem Informasi, 2001)
The business world today has undergone changes that have resulted in an achieved profits or losses suffered by the company, here the required financial management decisions for the progress of the company in the future. Companies which have assets or property in this case is called fixed assets is essential to undergo the business. From the author's desire to give information in accounting related to the values of depreciation per year. Due to the assets, that will definitely be experiencing depreciation in value will gradually decrease regularly. From here the residual value depreciation value of existing enterprise should perform the next steps for the progress of the company in the future.